2020
DOI: 10.1111/1749-4877.12489
|View full text |Cite
|
Sign up to set email alerts
|

Radicle pruning by seed‐eating animals helps oak seedlings absorb more soil nutrient

Abstract: Although radicle pruning has well been observed in plant-animal interactions, research has not been conducted to determine how radicle pruning by seed-eating animals regulates nutrition mobilization of cotyledonary reserves and absorption of soil nutrients. We used stable nitrogen isotopes to test how acorns of early-germinating oak species (Quercus variabilis, Q. aliena, and Q. mogolica) trade off nutrients in the cotyledons and those in the soil in response to radicle pruning by seed-eating rodents. Radicle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Consequently, 40-50% of the cotyledon dry mass was lost 10 weeks after germination. These results coincide with the previous studies on a variety of white oak species [22][23][24]36,37]. Compared to Q. variabilisand Q. serrataproducing nondormant acorns, acorns of Q. accutissima and C. glauca remained dormant and failed to protrude the robust taproots throughout the autumn and winter.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consequently, 40-50% of the cotyledon dry mass was lost 10 weeks after germination. These results coincide with the previous studies on a variety of white oak species [22][23][24]36,37]. Compared to Q. variabilisand Q. serrataproducing nondormant acorns, acorns of Q. accutissima and C. glauca remained dormant and failed to protrude the robust taproots throughout the autumn and winter.…”
Section: Discussionsupporting
confidence: 91%
“…While seed germination schedules (e.g., delayed seed germination and/or seed dormancy) usually cause seed dispersal differed in time, i.e., temporal dispersal [19,20]. Acorns of most white oak species and some intermediate oaks exhibit no dormancy and germinate rapidly in autumn [21][22][23][24]. In contrast, acorns of red oak species exhibit a delayed germination requiring a period of cold stratification before germination is possible [25].…”
Section: Introductionmentioning
confidence: 99%
“…We infer that radicle-pruning behavior may be more widespread in rodents and in a wide range of regions (Jansen et al, 2006;Cao et al, 2011;Yang et al, 2012). Furthermore, our results showed that radicle pruning did not negatively affect seed germination, suggesting that radicle pruning may not serve as an effective strategy for hoarding rodents to counter rapid germination of white oak species (Yang et al, 2012;Zhang et al, 2016;Yi et al, 2021).…”
Section: Radicle Pruning Of Sympatric Rodent Speciesmentioning
confidence: 76%
“…In North America, for example, several rodent species (including southern flying squirrels ( Glaucomys volans ), eastern chipmunks ( Tamias striatus ), and white-footed mice ( Permomycus leucopus )) selectively cache RO acorns over WO ( Steele et al., 2006 ). Likewise, these and other species in both North America and Asia rely on other strategies to manipulate scatter hordes of early germinating seeds, such as pruning acorns from developing taproots or repeated pruning of taproots or epicotyls ( Jansen et al., 2006 ; Cao et al., 2011 ; Yi et al., 2021 ). Therefore, it is not clear whether sympatric rodents adopt different foraging strategies for seed germination.…”
Section: Introductionmentioning
confidence: 99%
“…Under predation pressure by rodents, seeds have evolved into a series of strategies to escape rodent predation, such as resistance (Perea et al., 2011 ; Steele et al., 1993 ; Xiao et al., 2007 ), tolerance (Chen et al., 2012 ; Yang et al., 2023 ; Zhang et al., 2016 ; Zhang & Zhang, 2008 ), high capacity of regeneration (Cao et al., 2011 ) or seed cloning (Wang et al., 2021 ) or fast germination (Li et al., 2023 ). The tolerance mechanism allows seeds to maintain the ability to germinate and grow into seedlings even after being partially consumed, as long as the embryo remains intact (Mack, 1998 ; Vallejo‐Marin et al., 2006 ; Yi et al., 2021 ). Tolerance of seeds depends on the extent of damage, location of damage and species traits (Vallejo‐Marin et al., 2006 ).…”
Section: Introductionmentioning
confidence: 99%